Chatter-free tool orientations during five-axis ball-end milling of curved thin-walled parts - Dazhen, Wang; Weijun, Tian; Jinhua, Zhou; Junxue, Ren (International journal of advanced manufacturing technology, 2024)
Tool orientation is an important factor for improving machining stability in five-axis milling. However, there is still a lack of tool orientation planning strategy that is applied to the milling of curved thin-walled parts. This paper proposes a process mechanics-based method to optimize tool orientation to suppress chatter during five-axis ball-end milling of thin-walled parts. First, a coupling dynamic model considering both the flexible tool and workpiece is presented in the tool coordinate system, the model can predict the cutting stability of the entire process of milling thin-walled parts. Then, a binary search algorithm-based single-frequency method is presented to calculate limiting cutting depth. The method does not rely on the initial cutting depth and the increment of cutting depth which selected for calculation, the proposed method can expedite the convergence process for calculating the limiting cutting depth. Moreover, an iterative strategy of first generating smooth tool orientations through the representative tool orientations (RTOs) of typical cutter locations (CLs), and then checking the machining stability and adjusting the tool orientations is proposed to generate chatter-free tool orientations along the tool path. A machining stability factor is proposed to select tool orientation, and the tool orientation with a higher value of the machining stability factor is selected as the RTO. The proposed method only needs to obtain the chatter-free tool orientation regions at typical CLs, the calculation process is rapid. The proposed method has been experimentally proven in five-axis ball-end milling of the block workpiece and curved thin-walled part.